Teori Pemberlakuan Hukum Islam dan Implikasinya terhadap Pembentukan Hukum Positif di Indonesia - Pratama, Aan; Rahman R, Abd.; HL, Rahmatiah (Media Hukum Indonesia (MHI), 2026)
The history of the development of Islamic law in Indonesia demonstrates a long dynamic process involving interactions among customary law, colonial law, and Islamic law. The application of Islamic law in Indonesia reflects not only religious aspects but also legal politics and state policies across different periods. Through theories of legal applicability such as Receptio in Complexu, Receptie, and Receptio a Contrario, it is evident that the position of Islamic law has experienced fluctuations within the national legal system. The Receptio in Complexu theory places Islamic law as the law applicable to its adherents, whereas the Receptie theory holds that Islamic law applies only if it is accepted by customary law. Meanwhile, the Receptio a Contrario theory affirms the supremacy of Islamic law over customary law for Muslims. The implementation of these theories has had a significant impact on the formation of positive law in Indonesia, such as Law Number 1 of 1974 on Marriage, Law Number 7 of 1989 on the Religious Courts, and the Compilation of Islamic Law (KHI). This study employs a qualitative descriptive method with a library research approach. The results show that theories on the applicability of Islamic law have played an important role in laying the foundation for the integration of Islamic values into the national legal system as well as into the social life of Indonesian Muslims.